Knowledge, Attitude and Practice towards Cervical Cancer among Reproductive Health Clients at the University of Science & Technology Hospital-Sana'a in Yemen - Abdul-Aziz, Maha (University of Science and Technology, 2014)
Background: Cervical Cancer is the second most common cancer among women worldwide. It is mostly caused by a virus called human papilloma virus (HPV). Females can get HPV by having sexual contact with someone who has it. It is one of the most preventable cancers by the routine cervical screenings and HPV vaccination. Aim: To assess the knowledge, attitude and practice towards cervical cancer among women visiting the University of Science & Technology Hospital- Sana'a. Methods: This is a descriptive cross-sectional study carried out in July, 2009 on women visiting the gynaecological out-patient clinic at the University of Science & Technology Hospital- Sana'a. A sample of 283 women was selected by convenience sampling. The study was conducted by means of a questionnaire survey. Results: Among the participants, 80.6% (228) had various levels of knowledge about cervical cancer. 42.3% knew that viral infection by HPV may be the cause of cervical cancer. As regard to the clinical presentation of cancer cervix, women knew that vaginal bleeding (77.2%), pelvic pain (43.9%), menstrual disturbances (35.1%) were the commonest. As for prevention of cervical cancer, 72% had some knowledge; 59% have an idea about the periodic cervical screening, while only 18% knew the HPV vaccine. Conclusion: Women in this study had a satisfactory knowledge and awareness about cervical cancer; its risk factors, clinical presentation, prevention. However, their knowledge on the management of cervical cancer was mostly false.